2005
DOI: 10.2307/3647698
|View full text |Cite
|
Sign up to set email alerts
|

Priming Gender: Campaigning on Women's Issues in U.S. Senate Elections

Abstract: The gender gap has been an important feature of American elections since 1980. Yet, most explanations for the effects of gender on voting behavior focus on differences between men and women without taking account of how campaign strategies may serve to highlight or mask these differences. I examine how Senate candidates act strategically in deciding whether and how to target women voters. I find that candidates make these decisions based largely on two factors: (1) the importance of these issues to the state's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 8 publications
(11 reference statements)
0
34
0
Order By: Relevance
“…9 vote for that candidate. If the group appeals of identity-based targeting are not as crucial as we believe, we may see the ad prime particular issues or image dimensions related to the communicated issues or image characteristics, as Schaffner (2005) does. However, as we argue earlier, we believe that these appeals prime identity, which improves candidate evaluations and the probability that a targeted individual will vote for the candidate.…”
Section: Effects Of Identity-based Targetingmentioning
confidence: 79%
See 2 more Smart Citations
“…9 vote for that candidate. If the group appeals of identity-based targeting are not as crucial as we believe, we may see the ad prime particular issues or image dimensions related to the communicated issues or image characteristics, as Schaffner (2005) does. However, as we argue earlier, we believe that these appeals prime identity, which improves candidate evaluations and the probability that a targeted individual will vote for the candidate.…”
Section: Effects Of Identity-based Targetingmentioning
confidence: 79%
“…There have been many demonstrations of issue based-targeting, where the campaign identifies a particular issue, and it primes voters to consider that issue more in their overall evaluations of a candidate (e.g., Hillygus and Shields 2008;Johnston et al 1992). In particular, Schaffner (2005) finds that in districts where women are a significant portion of the electorate, candidates emphasize women's issues, which then in turn improves the likelihood that women voters will 2 Tolleson-Reinhart 14 argues that group consciousness includes an identification with others that are similar, a positive affect towards them, and an understanding of interdependence with like-others. 9 vote for that candidate.…”
Section: Effects Of Identity-based Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Campaigning on women's issues is not a new strategy for candidates of both genders, but the two main political parties approach it differently. Schaffner (2005) observed that candidates focus more on female issues when the state's population is more concerned with them, and women become more likely to vote as Democrats when women's issues are at the forefront of the campaign's focus. A former senator in the Texas legislature, Davis decided to run for the open governor's seat after Rick Perry announced he would not seek another term.…”
Section: Gender Within Political Partiesmentioning
confidence: 99%
“…This could be due to the perception of Republican-owned traitstied to issues of national securitybeing more important to address Smith et al, 2007). In the Senate, Schaffner (2005) found Democratic women more likely to campaign on education, health care, and childcare than Democratic men. In the House, Democratic women were more likely to campaign on social issues and abortion than Democratic men; Republican women were more likely than Republican men to campaign on abortion .…”
Section: Gendered Partisanshipmentioning
confidence: 99%